Acceleration of One Indonesian Data through Collaborative Governance in Indonesia - Susniwati Susniwati; Moh. Zamili (Universitas Muhammadiyah Gorontalo, 2022)
This study aims to analyze the acceleration of one data Indonesia through collaborative governance. Data quality is a necessity for every country. Unfortunately, data accuracy between regions down to the central level faces various problems. Indonesia already has the One Data Indonesia program but the development and progress of the program being managed requires adaptive and flexible collaboration. Qualitative research uses data collection techniques of observation, interviews, and documentation. The study’s results found (1) Challenges in solving substantive problems by identifying the problem of differences in data from government institutions. The problem is that each institution defines the problem from its point of view. So that the problem will be increasingly difficult to define because of the different perspectives of the parties collaborating on an issue (2) Challenges in the collaboration process, the issue of open data, data validity, and single data are faced with many problems, one of which there are 24,400 thousand applications that stand alone so that integration becomes difficult. There is a sectoral ego where the institution or agency is unwilling to share its data. (3) The challenge of multi-relational accountability in implementing the acceleration of SDI at the provincial, city, and district levels. Many regions still have not carried out the mandate of the Presidential Regulation on SDI due to various reasons.